Immobilization and stabilization of a bimolecular aggregate of the lipase from Pseudomonas fluorescens by multipoint covalent attachment - De Lima, Lionete Nunes; Aragon, Caio C. [UNESP]; Mateo, Cesar; Palomo, Jose M.; Giordano, Raquel L.C.; Tardioli, Paulo W.; Guisan, Jose M.; Fernandez-Lorente, Gloria (My University, 2013)
The soluble lipase from Pseudomonas fluorescens (PFL) forms bimolecular aggregates in which the hydrophobic active centers of the enzyme monomers are in close contact. This bimolecular aggregate could be immobilized by multipoint covalent linkages on glyoxyl supports at pH 8.5. The monomer of PFL obtained by incubation of the soluble enzyme in the presence of detergent (0.5% TRITON X-100) could not be immobilized under these conditions. The bimolecular aggregate has two amino terminal residues in the same plane. A further incubation of the immobilized derivative under more alkaline conditions (e.g., pH 10.5) allows a further multipoint attachment of lysine (Lys) residues located in the same plane as the amino terminal residues. Monomeric PFL was immobilized at pH 10.5 in the presence of 0.5% TRITON X-100. The properties of both PFL derivatives were compared. In general, the bimolecular derivatives were more active, more selective and more stable both in water and in organic solvents than the monomolecular ones. The bimolecular derivative showed twice the activity and a much higher selectivity (100 versus 20) for the hydrolysis of R,S-2-hydroxy-4-phenylbutyric acid ethyl ester (HPBEt) in aqueous media at pH 5.0 compared to the monomeric derivative. In experiments measuring thermal inactivation at 75 °C, the bimolecular derivative was 5-fold more stable than the monomeric derivative (and 50-fold more stable than a one-point covalently immobilized PFL derivative), and it had a half-life greater than 4 h. In organic solvents (cyclohexane and tert-amyl alcohol), the bimolecular derivative was much more stable and more active than the monomeric derivative in catalyzing the transesterification of olive oil with benzyl alcohol. © 2012 Elsevier Ltd. All rights reserved.
Keywords: Enzyme immobilization and stabilization; Improved enantioselectivity; Lipase aggregates; Pseudomonas fluorescens lipase; Active center; Alkaline conditions; Aqueous media; Benzyl alcohol; Covalent linkage; Ethyl esters; Glyoxyl; Multipoint attachment; Multipoint covalent attachments; Pseudomonas fluorescens; Soluble enzymes; Soluble lipase; Terminal residues; Tert-amyl alcohols; Thermal inactivation; Triton X-100; Alkalinity; Amino acids; Bacteria; Enzyme immobilization; Monomers; Organic solvents; Stabilization; Vegetable oils; Aggregates